Burden of Regulation on the performance and growth of SMEs: Empirical analysis in Silte Zone, Southern, Ethiopia - Ali Nasir; Tarik Kechema (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The main purpose of this study was to investigate the perception to wards the burden of regulation on the performance and growth of SMEs in Silate Zone, SNNPRS, Ethiopia . To attain the intended objective the study used quantitative research of descriptive statistics and multiple regression for pooled least squares estimations method used. Bassed on the accessed data, there were 1718 formally registered SMEs in the form of private limited companies and sole proprietor types of legal status in Silte Zone, SNNRS from 2016 to 2021. The result of this mixed approach explores that SMEs face challenges from different factors but, they perceived challenges from regulatory burden outweigh other factors. Pooled multiple regression for all independent and control variables simultaneous indicated that, except for inapproprate enforcement of regulatory fream works (0.157) and compatibility in the globa market of SMEs rate (0.213) all variables had negative coefficient. At the same time, apart from debt ratio p-value (0.258) all variables are significant at 1 percent degree of freedom. The value of adjusted R2 is 75.2 percent; while Durbin-Watson and F-statistic are, 1.47 and 25.81 respectively. The result also identifies mechanisms mostly used by SMEs to mitigate problems from regulations and how much the regulators have smooth contact with them and to what extent the regulators made inspection, consultation and communication. Moreover, the result identifies the relation between regulations and SMEs performance and growth based on their view i.e. they have positively related each other. As a whole, the study suggests a series of measures which could be taken by the government policy makers/regulators and for SMEs. This measure includes to adopt government impact assessment task force and review the existing regulations how much they enable and constrain businesses and at the same manner suggest for SMEs to incorporate different mechanisms to comply with regulation rather than rely more on specific mechanisms.